Svenskt instrumentmakeri 1720-1800: En preliminär översikt - Helenius-Öberg, Eva (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2025)
This study is a survey of instrument making in Sweden between 1720 and 1800, its structure, conditions, and factors governing its development. Owing to the limited number of Swedish made instruments surviving from the period before about 1750, the account is primarily based on an examination and analysis of archival sources (administrative records). The material (i. e. a combination of written sources and surviving instruments) indicates that before 1720 workshops were concentrated to Stockholm. The exact number was thirteen. Outside the capital we know (at present) of only three workshops where instruments may have been made. In Stockholm, makers of stringed and plucked instruments (seven in number) appear to predominate between about 1650 and 1720. Tables 1 and 3 list privileges granted and workshops known to have existed during the period of this study. Closer study reveals that most of these workshops were run by organ builders, makers of stringed and plucked instruments and makers of keyboard instruments (other than organs) in that order. Other workshops specializing in wind and percussion instruments and in mechanical instruments and strings were few and far between. it should be noted, however, that instruments and accessories of these kinds were manufactured at brass foundries, watchmakers’ and by makers of stringed and plucked instruments, so that the exact number of workshops cannot be ascertained; all we can say is that their output must have been greater than has previously been supposed. Stockholm continues to dominate the scene during the 18th century, but there is also more widespread activity in the provinces. Of the 26 clavier makers known to us today, 17 were active in Stockholm and 9 in the provinces, while 18 out of a total of 31 known makers of stringed and plucked instruments were active in Stockholm and 13 in the provinces. Of the 18 master organ builders to whom privileges were granted, 5 had their workshops in Stockholm and one in Finland (Turku) while the remainder were active in the Swedish provinces. Where organ building is concerned, something of a partition of the country into "territories" can be observed, although the organ builders originally granted exclusive privileges covered the entire country, Finland included. Most wind instruments were made in Stockholm; in addition, there was Ek’s workshop in the town of Arboga as well as certain mining and manufacturing communities (bruk in Swedish) and turneries. As far as we know, mechanical instruments were manufactured in Stockholm and nowhere else. Workshops specializing in string making were also located in Stockholm, with few exceptions. Thus compared with the 17th century, the 18th brought a considerable increase and widening of the number of instrument makers’ workshops in Stockholm, and it also witnessed a spread of these workshops to the provinces, mostly to towns (quite often staple towns) in southern Sweden, on the Östergötland plain and in the lake Mälar provinces, i.e. the main population centres of the inhabited and cultivated parts of Sweden at that time. Section 5.2 contains an analysis of data from the Hallrätt guild court of Stockholm showing that the declared values of newly manufactured musical instruments (i.e. excluding payment for repairs, tuning etc.) describes a graph line running more or less parallel to the general trend in manufacturing. During the period under consideration there was a distinct and at times steep rise, the first peak in 1760 being followed by a trough during the ensuing decade and then by a new manufacturing peak in 1776. The real "take-off year for instrument manufacturing came in 1755. Before 1756 instruments were imported in quite considerable numbers (section 4.2) and native output was small. The latter, however, began to rise after 1755. Thus the graph lines for imports and native manufacture intersect in the mid- 1750s, and the only reasonable explanation would seem to be that the ban on imports of musical instruments, imposed in 1756, was reasonably effective during the 18th century, with the result that demand for instruments, if it remained unaltered or (towards the end of the century, possibly earlier) rose, was catered for by domestic manufacture accept as regards wind instruments. Thus the 18th century was definitely a period of expansion in Swedish instrument making, this is reflected by the number of workshops, their location and the breadth, quantity and quality of their output. The output graph referred to above and based on independent figures, confirms the picture conveyed by statements from contemporary administrative authorities (quoted in section 3). The following theses can therefore be propounded At the beginning of the Era of Liberty (ca 1720), instrument making in Sweden was still organized on a relatively modest scale and for the most part confined to Stockholm. The Era of Liberty (1720-1771) itself saw a rise in the number of workshops and in their output, coupled with an expansion into the provinces, despite certain periods of stagnation. The Gustavian period (1771-1809) was the first period of quantitative and qualitative prosperity in Swedish instrument making. Compared with other native manufacture and with European instrument making, the growth of instrument making in Sweden came very late. One can discern two main factors behind the expansion. The first of these is the state of music in Sweden, which was characterized among other things by the rise of public concerts, the increasing popularity of amateur music making and changes of orchestral resources, especially as regards the instrumental make-up of military music. The second factor was the economic policy of the time, which fostered native crafts and restricted imports. Perhaps the fall of Sweden as a great power in 1718, with the loss of the continental territories, also played a part in this process. Before then, with Swedish instrument making in its infancy, instruments were perhaps more conveniently and more cheaply obtainable from or through the Swedish possessions across the Baltic and in Germany. If so, political upheaval contributed to the development of Swedish instrument making.